2019
DOI: 10.1177/1010428319892790
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological role of endogenous irisin against tumorigenesis and metastasis: Is it a potential biomarker and therapeutic?

Abstract: In the last few decades, there has been notable progress in understanding the molecular and cellular basis of the complex process involved in cancer. In this context, tumor-promoting inflammation, dysregulation of apoptotic signaling, tissue invasion and metastasis, and cancer microenvironment have recently attracted interest from researchers. Irisin is a hormone released by muscles during exercise and it directly acts on key functional cells involving energy metabolism and homeostasis. Recently, many studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…As mentioned above, irisin is a type I transmembrane messenger protein that is mainly secreted by the skeletal muscle and stimulates “browning” and thermogenesis in fat tissue [ 53 ] and induces changes in different tissues in response to exercise [ 39 , 44 ]. Currently, there is no irisin receptor identified.…”
Section: Irisinmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, irisin is a type I transmembrane messenger protein that is mainly secreted by the skeletal muscle and stimulates “browning” and thermogenesis in fat tissue [ 53 ] and induces changes in different tissues in response to exercise [ 39 , 44 ]. Currently, there is no irisin receptor identified.…”
Section: Irisinmentioning
confidence: 99%
“…The studies are presented chronologically, and summary data tables are included. It should be noted that a number of related past reviews exist [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]; however, the present review provides updated information and adds to the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Irisin was found to contrast denervation and oxidative stress [27,116], suggesting a beneficial role in ALS. Recent studies showed that irisin expression increased in patients affected by metabolic disorders and cancer cachexia [117]. Moreover, it was found increased in blood of ALS patients with great disability [118].…”
Section: Preclinical Studies and Proposed Drugs Able To Restore Skele...mentioning
confidence: 99%
“…Conversely, expression of irisin was reduced in patients with type 2 diabetes and non-alcoholic fatty liver disease. Most recent studies have demonstrated that serum irisin concentration was reduced in patients with breast cancer and exerts inhibitory effect on malignant breast cancer cells [117]. In this regard, further study of these pathways may be useful to assess the role of this myokine in a situation of inactivity such as ALS.…”
Section: Preclinical Studies and Proposed Drugs Able To Restore Skele...mentioning
confidence: 99%
“…It suppresses tumor-promoting inflammation, inhibits metastasis, and increases apoptosis. 142 Skeletal muscle is the main source of irisin secretion (about 72%), 139 and age-related sarcopenia may decrease circulating irisin levels in the elderly. 143 On the other hand, exercise may have a potential to induce irisin's secretion 139,144 which could contribute to its tumor-suppressing effects.…”
Section: Do We Know How Exercise Fights Chemotherapy Related Toxicity?mentioning
confidence: 99%